2018
DOI: 10.22159/ajpcr.2018.v11i10.26289
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Magnesium Sulfate With Glycerine Versus Cold Compress on Patients With Peripheral Intravenous Cannula Induced Phlebitis

Abstract: Objective: The objective of the study was to determine the effectiveness of magnesium sulfate with glycerine versus cold compress on patients with a peripheral intravenous cannula (PIVC) induced phlebitis. Methods: A quasi-experimental pre-test post-test study on 60 subjects, 30 in each group, with interventions magnesium sulfate with glycerine application to one group and cold compress to another group of patients with PIVC induced phlebitis was done in a tertiary care hospital, Kerala. Purposive sampling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Other various studies also agree that there is a significant decrease in post test score after magnesium sulphate application in the treatment of phlebitis in adults. [13][14][15]21,22 Another study in China, showed similar findings that phlebitis was significantly reduced by external application of magnesium sulphate. 16 The study shows a significant difference in reduction of VIP score at 12 hours (p = 0.403) and 24 hours (p = 0.002) in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…Other various studies also agree that there is a significant decrease in post test score after magnesium sulphate application in the treatment of phlebitis in adults. [13][14][15]21,22 Another study in China, showed similar findings that phlebitis was significantly reduced by external application of magnesium sulphate. 16 The study shows a significant difference in reduction of VIP score at 12 hours (p = 0.403) and 24 hours (p = 0.002) in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…Concerning the mode of administration, some studies (Basu et al, 2017; Selva Grace et al, 2020; Soloman et al, 2015; Yadav et al, 2016; Yambem et al, 2015) provided no information In this respect, magnesium sulphate‐glycerine was administered in solution form (Amuda et al, 2019; Packialakshmi & Vidhya, 2017; Varghese & Moly, 2018) through compress and bandage 2 or 3 times a day for 2 or 3 days, in ointment form 3 times a day for 3 days (Jayabharathi, 2015; Rukhsana et al, 2016), and with a bandage and raised limb twice a day for 2 days (Ravindra & Patel Krupa, 2015). Magnesium sulphate was applied every 2 h for 2 days in solution form with a compress, and the limb was raised, wrapped in plastic and immobilised (Wan, 2018), or it was applied in ointment form with a gauze dressing twice or 3 times a day for 2 or 3 days (Sharma, 2016; Vidhya, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 9 studies which considered anti‐inflammatories, 7 reported an improvement in symptoms: magnesium sulphate‐glycerine (Packialakshmi & Vidhya, 2017; Ravindra & Patel Krupa, 2015), vs. the application of cold (Varghese & Moly, 2018) and vs. heparinoids (Amuda et al, 2019; Jayabharathi, 2015; Selva Grace et al, 2020; Yambem et al, 2015). Magnesium sulphate without glycerine obtained a better response than heparinoids and the application of cold (Sharma, 2016) and aloe vera (Vidhya, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations